A revision of the Patagonian predaceous midges of the genus Palpomyia Meigen (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2009)
This revision of the predaceous midges in the genus Palpomyia Meigen inhabiting the Patagonian region of Argentina and Chile recognizes eight species, provides diagnoses, descriptions, illustrations and a key to all species, as well as new distributional records of previously described species. Four new species are described and illustrated: P. mapuche, P. marinoi, P. septentrionalis and P. yamana (spp. n.). Palpomyia patagonica Ingram and Macfie and P. subfuscula I. and M. are redescribed and illustrated, the previously unknown male of P. patagonica is described and illustrated, and P. subaspera (Coquillett) is recorded for the first time from Patagonia. Palpomyia chilensis Ingram & Macfie is transferred to Austrosphaeromias Spinelli (n. comb.)